PURINE ALKYLATING AGENTS 2 , 6-DIAMINO-8-HALO ALKYL PURINES (POTENTIAL ANTI - MALARIALS) (Journal of Sciences, Islamic Republic of Iran)
Haloalkyl purines i.e. 2,6-diamino-8-(chloromethyl) purine 10; 2, 6-diamino-X- (chloromethyl) purine 17; 2,6-diamino-8-(chloropropylp) urine 18; were synthesized by two distinct but facile methods. The N-alkylating potential of 2, 6-diamino-8- (chloromethyl) purine was investigated. The following products 2,6-diamino-8-(Nbenzyl- N-methyl) purine 11; 2,6-diamino-8-(4-nitro anilinomethyl) purine 13; 2,6- diarnino-8-(piperidino-N-methyl)Purine 14; 2,6-diamino-8-(3,4,5-trimethoxyanilinomethyl) purine 12; of N-alkylation are reported. Antifolate activities obtained for these compounds are also reported. 2,6-diamino-8-(3,4,5-trimethoxyanilinom ethyl) purine demonstrated significant biological activity (ID = 1 x10 ). Most antifols are also antimalarials e.g. trimethoprim and pyrimethamine, and therefore these 8-haloalkyl purines may be effective antimalarials if modified by appropriate reagents